Factors Predicting Health-Related Quality of Life among Patients with Myocardial Infarction in Myanmar - Su Kalayar Hlaing (2019)
Purpose: To examine the predictive power of age, sex, depression, and social support on health-related quality of life among patients with myocardial infarction in Myanmar. Design: Predictive correlational design. Methods: The sample consisted of 100 myocardial infarction patients diagnosed for at least three months and came to follow-up at Cardiology Clinic, Yangon General Hospital, Myanmar. Data were collected by using demographic form, the World Health Organization Quality of Life Questionnaire (WHOQoL-BREF), the Patients Health Questionnaire (PHQ-9), and the Social Support Questionnaire. Descriptive statistics and multiple regression analysis were used for data analysis. Main findings: The mean score of the overall health-related quality of life was found to be moderate (M = 82.02, SD = 8.84). The mean age of the samples was 60.6 years (SD = 8.98) and 67% were men. The majority of the sample had mild depression (M = 5.23, SD = 6.10). Sixty percent of them perceived high-level social support. In multiple regression analysis, age, sex, depression, and social support jointly accounted for 34.1% of the variance in overall health-related quality of life (R2 = .341, F(4, 95) = 7.327, p < .001). Depression was the only one variable significantly predicting health-related quality of life (β = - .505, p < .001). Conclusion and recommendations: Findings from this study revealed moderate health-related quality of life in Myanmar patients with myocardial infarction and depression was the important predictor. The patients should be assessed for depression regularly to reduce depressive symptoms and improve health-related quality of life.